“Вовча зоря” and “Сталінка”: The lost generation through the eyes of Yevgen Pashkovsky and Oles Ulyanenko: Вовча зоря vs Сталінка: про загублене покоління очима Євгена Пашковського та Олеся Ульяненка - Horniatko-Szumiłowicz, Anna (Przegląd Wschodnioeuropejski, 2020)
The subject of the paper is to compare the two contemporary novels – “Вовча зоря” (1991) and “Сталінка” (1994). The research question concernes the portrayal of the lost generation by the two prominent Ukrainian writers, also authors of the aforementioned novels – Y. Pashkovsky (b. 1962) and O. Ulyanenko (1962-2010). The research methodology includes the historical approach, the theoretical approach, the analytical method and the comparative approach. Research involved an analysis of source material, specifically the avalaible critical pieces (papers, reviews, interviews). Results learned from the research allow us to determine that despite a few differences in world creation and style, both writers accurately portrayed the Ukrainian lost generation of the 1980s, including their misplaced values and lost direction.